2020
DOI: 10.1039/d0em00057d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging and weathering on immobilization of trace metals/metalloids in soils amended with biochar

Abstract: Biochar is an effective amendment for trace metals/metalloids (TMs) immobilization in soils. The capacity of biochar to immobilize TMs in soil can be positively or negatively altered due to the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 164 publications
0
10
0
Order By: Relevance
“…The composting thermophilic biological degradation process can inactivate helminth eggs to the World Health Organisation’s recommended levels for safe agricultural use 34 , 35 . Considerable studies have demonstrated the benefits of co-compost application on land in terms of improved soil water-holding capacity, nutrient retention, and soil structure 36 39 . Compost application complements and supplements the use of chemicals fertilizers by augmenting their agronomic efficiency 4 , 10 , 40 .…”
Section: Introductionmentioning
confidence: 99%
“…The composting thermophilic biological degradation process can inactivate helminth eggs to the World Health Organisation’s recommended levels for safe agricultural use 34 , 35 . Considerable studies have demonstrated the benefits of co-compost application on land in terms of improved soil water-holding capacity, nutrient retention, and soil structure 36 39 . Compost application complements and supplements the use of chemicals fertilizers by augmenting their agronomic efficiency 4 , 10 , 40 .…”
Section: Introductionmentioning
confidence: 99%
“…The contrasting properties between macro- and nano-scale materials have resulted in proposals for separate regulatory frameworks (Kookana et al 2014 ). There are recent investigations into aging and weathering effects on bulk biochar applications (Zhong et al 2020 ), but there is a need for increased focus on the long-term effects of PBNPs and their lifecycle following release from bulk applications. These should include real-world sampling for PBNPs downstream from previous bulk applications as well as testing of aquatic organisms.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…Although there is no direct comparison of reactivities between PBNPs purposefully produced (e.g., ball-milled) and those leached after bulk material application and derived through natural processes, it is safe to assume that mechanical breakage is comparable to abrasion and other physical stresses imposed in the environment. Recently, Zhong et al ( 2020 ) investigated the weathering and aging effects on bulk biochar structure and surface chemistry used in soil amendment, which may additionally include degradation induced by microbial communities. To our knowledge, there has been no review of the impacts of PBNPs produced and released in the environment from biochar and activated carbon used in remediation, soil amendment, and wastewater treatment applications.…”
Section: Introductionmentioning
confidence: 99%
“…12 There was evidence of cracking and fracturing of the biochar surface with alternate wetting and drying. 13 However, so far the influences of soil compositions on biochar stability was not taken seriously or researched quantitatively. Because it was difficult to apply a single conceptual model or a precise numerical model to complex soil system.…”
Section: Introductionmentioning
confidence: 99%
“…Water rinsing likely removed the fine biochar particles that were loosely attached to the biochar particle surface 12 . There was evidence of cracking and fracturing of the biochar surface with alternate wetting and drying 13 . However, so far the influences of soil compositions on biochar stability was not taken seriously or researched quantitatively.…”
Section: Introductionmentioning
confidence: 99%